Ω-3 index as a prognosis tool in cardiovascular disease. Issue 5 (September 2017) - Fielding, Barbara A.
Abstract : Purpose of review: In 2004, the 'Ω-3 index' was described as the sum of eicosapentaenoic acid (EPA, 20 : 5 n-3) and docosahexaenoic acid (DHA, 22 : 6 n-3) in red blood cells (RBCs) as an index of coronary heart disease mortality. This review outlines new evidence to support the Ω-3 index as a tool to inform disease prognosis. Recent findings: Recent studies have reported differential metabolism of EPA and DHA. High-dose supplementation with EPA and DHA led to increased levels of RBC DHA that were associated with decreased liver fat. EPA and DHA in RBCs were associated with reduced mortality in a prospective study of patients with cardiac disease; the strongest association was with EPA. A diet containing 9.5-g α-linolenic acid lead to an increase in EPA but not DHA status in middle-aged women. Summary: Dietary intake or supplementation studies with n-3 fatty acids should include measurement of n-3 status in a standardized way. The Ω-3 index, reflecting EPA and DHA status throughout the body, is convenient and may be appropriate in some cases, but as EPA and DHA assimilate differently in membranes, and have different potency, measurement of individual fatty acid composition in RBCs may be more informative.